Prarancangan Pabrik Nitrobenzena Dari Benzena Dan Asam Campur Dengan Proses Batch Kapasitas 325.000 Ton/Tahun - Idrus, Mgs. Ahmad, Ir. Herry Purnama, M.T., Ph.D, M. Mujiburohman, S.T., M.T.,Ph.D (2016)
ABSTRACT Nitrobenzene is a raw material for making aniline. Benzene and nitrobenzene plant for sour mix established because the need for such materials is increasing from year to year. Nitrobenzene plant is designed to meet the needs of the country and the role in the possibility to be exported. Nitrobenzene plant is designed with a capacity of 325.000 tonnes a year with operated for 330 days a year. Nitrobenzene manufacturing process using a direct nitration process liquid phase mole ratio of benzene : each nitrate = 1,05 : 1. The reaction is exothermic and run with batch reactors, liquid-liquid phase, irreversible and kept isothermal operating conditions (50oC) and a pressure of 1 atm. Nitration of benzene with mixed acid, with this batch process using a mixed acid at 56-60% H2SO4, 27-32% HNO3, 8-17% H2O. The reaction temperature is 50-55oC, product out nitrator separated in the separator. Nitrobenzene in the neutralization products, 95-98% yield and reaction time in batches ranging from 2-4 hours. From the analysis of the economic, nitrobenzene plant requires a fixed capital of 85,198,785,000.00 IDR fixed capital and working capital of 391,075,579,565.48 IDR. Profit befor tax of 2.289.294.572.541,13 IDR, profit after tax 1,831,435,658,032,90 IDR a year. This feasibility analysis gives the result that the percent Return On Investment (ROI) before tax amounted to 20,05% and after tax of 15,42% Pay Out Time (POT) before tax of 0,48 years, while after tax of 2,03 years, Break Even Point (BEP) amounted to 15,02 capacity, and Shut Down Point (SDP) amounted to 18,22 capacity, Discounted Cash Flow (DCF) amounted to 25,60% based on the data above, the benzene and nitrobenzene plant sour mix is quite interesting to be established.